2022
DOI: 10.3389/fphar.2022.820210
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Delivery of Galanin 2 and Neuropeptide Y1 Agonists Enhanced Spatial Memory Performance and Neuronal Precursor Cells Proliferation in the Dorsal Hippocampus in Rats

Abstract: A need for new therapeutic approaches are necessary for dementia conditions and memory deficits of different origins, such as Alzheimer's disease. There is complex pathophysiological mechanisms involved, affecting adult hippocampal neurogenesis, in which neuropeptides and its neurogenesis regulation seem to participate. Neuropeptide Y(NPY) Y1 receptor (Y1R) and galanin (GAL) receptor 2 (GALR2) interact in brain regions responsible for learning and memory processes, emphasizing the hippocampus. Moreover, a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 74 publications
6
33
0
Order By: Relevance
“…Following intranasal delivery of GALR2 and Y1R agonists we observed an increased cell proliferation in the ventral DG of the hippocampus by using the PCNA. In agreement, we have recently observed the ability of the coagonist intranasal infusion to enhance the cell proliferation in the DG of the dorsal hippocampus at 24 h (Borroto-Escuela et al, 2022). Previous work showed that icv infusion of GAL and the Y1R agonist-induced proliferation by using 5-bromo-2-deoxyuridine on the ventral hippocampus (Borroto-Escuela et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Following intranasal delivery of GALR2 and Y1R agonists we observed an increased cell proliferation in the ventral DG of the hippocampus by using the PCNA. In agreement, we have recently observed the ability of the coagonist intranasal infusion to enhance the cell proliferation in the DG of the dorsal hippocampus at 24 h (Borroto-Escuela et al, 2022). Previous work showed that icv infusion of GAL and the Y1R agonist-induced proliferation by using 5-bromo-2-deoxyuridine on the ventral hippocampus (Borroto-Escuela et al, 2021).…”
Section: Discussionsupporting
confidence: 87%
“…The doses indicated are based on previously published protocols (Borroto-Escuela et al, 2022;Serova et al, 2017).…”
Section: Assessment Of Ventral Hippocampus Activation After Intranasa...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 810–2 has a short half‐life 28 and has not yet been optimized for oral administration. However, intranasal delivery of galanin analogs 19,69 has been shown to facilitate blood–brain barrier penetration, reduce food intake, and improve memory. Intranasal formulation and delivery of LEV 70 also suggests the potential for this route of administration as part of a combinatorial treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The results of clinical trials are inconsistent, and it is likely that high doses are required to achieve a therapeutic effect, however, further investigation is necessary to make a meaningful conclusion [ 119 ]. Similarly, intranasal neuropeptide Y and galanin receptor agonists improved performance in memory retrieval tasks and increased cell proliferation in the dorsal hippocampus of rats [ 120 ].…”
Section: Intranasal Drug Deliverymentioning
confidence: 99%